Chronic abscess in isthmocele: a rare entity - Jacob, Sujamol; B. S., Lakshmi; S., Sujin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Uterine isthmocele, also known as caesarean scar defect or uterine niche is a triangular defect in the anterior uterine wall at the site of the previous caesarean scar, with its base communicating with the uterine cavity. It represents an inadequate healing of the myometrium following caesarean section. Transvaginal ultrasound (TVS), saline infusion sonohysterogram (SIS), hysterosalpingogram, hysteroscopy, and MRI are various modalities to make a confirmatory diagnosis. Medical or surgical management is undertaken depending on the size and type of defect. The aim is to manage symptomatic patients. But chronic presentation of isthmocele is very rare and hence difficult to diagnose. Hereby presenting this case report, where the isthmocele was presented as a chronic abscess. Hence reporting this case for early suspicion of isthmocele and prompt management.